Preliminary efficacy of aerobic training among university students with migraine symptoms: Study protocol for a pilot randomized controlled trial - Selvakumar, Kiruthika; Lee Fan, Tan; Chai Nien, Foo; Hou Kit, Mun (PloS one, 2023)
Migraine is a primary neurological headache. Treatment of this condition includes medications; however, these medications, when given for a longer duration, can have side effects. If migraine is left untreated or undiagnosed, it is reported that around 2.5% of individuals with migraine may develop to have a chronic condition. This study aims to analyse the preliminary effectiveness of aerobic training on migraine pain level, sleep quality, quality of life, and resting-state brain waves among university students with migraine symptoms. 88 university students with migraine symptoms are the target participants. 4 of 5 on the Migraine Screen Questionnaire, 5 of 7 on the International Classification of Headache Disorders 3rd edition (ICHD-3), and both genders aged 18-40 years will be included. The participants with a score of more than or equal to 5 on the visual aura rating scale, diagnosed with a secondary headache, pregnancy, medication for neurological and cardiorespiratory conditions, and unwilling to participate will be excluded. Based on the disability questionnaire, the participants will be randomly assigned to either of the three groups. The primary outcome is resting-state electroencephalography (EEG) brain, and the secondary outcomes are sleep quality, quality of life, and migraine pain level. The post-test assessments will be performed at week 6. After the primary EEG analysis using MATLAB, the amplitude, frequency, frequency band ratio, and power spectrum density will be analysed. Mixed design analysis and intention-to-treat analysis will be used to assess the efficacy of aerobic training. Migraines can be unpredictable, sometimes occurring without symptoms. If underdiagnosed or over-looked, it encompasses a serious of long-term effects. Hence with appropriate intervention, the symptoms can be prevented from worsening. But there is an unmet need for evidence-based non-pharmacological approaches to complement pharmacotherapy in migraine prevention. Moreover, an exercise intervention may be more suitable for people with migraine considering their tendency toward inactivity. Although some studies developed exercise programs for untrained patients with migraine, the outcome was primarily in terms of exercise capacity rather than the primary characteristics and secondary brain wave/ sleep quality changes, indicating the need for this study.